Serum ADAMTS-13 Levels as an Indicator of Portal Vein Thrombosis - Tomasz Mikuła; Joanna Kozłowska; Wojciech Stańczak; Mariusz Sapuła; Aleksandra Różyk; Alicja Wiercińska-Drapało (Gastroenterology Research and Practice)
Background. Coagulation disorders in patients with liver cirrhosis are a common clinical problem. Cirrhosis should be considered a state of impaired blood clotting or an imbalance of the whole coagulation system. Cirrhosis-induced coagulopathy encompasses disturbances in both the procoagulant and anticoagulant systems. This mechanism may promote the development of thrombosis with portal vein thrombosis (PVT), which is considered an obstacle to orthotopic liver transplantation (OLT). We assessed serum ADAMTS-13 levels in patients with decompensated liver cirrhosis, with and without PVT. Material and Methods. Serum ADAMTS-13 levels, age, platelet count (PLT), and INR (international normalized ratio) were evaluated in (n=64) patients with liver cirrhosis either with PVT (group 1, n=31) or without PVT (group 2, n=33). The results were compared with those from healthy volunteers (group 3, n=37). Liver cirrhosis was based on Desmet’s classification of chronic hepatitis in liver biopsy stage ≥ 3 or liver elastography F-score ≥ 3. Serum ADAMTS-13 levels were measured with Quantikine® ELISA Human ADAMTS13 Immunoassay, R&D Systems Inc. We used Welch’s F-test, Games-Howell, one-way ANOVA, Bonferroni test, and logistic regression to determine whether ADAMTS-13 levels were a predictor that was independent of MELD and Child-Pugh scores. All results (P<0.05) were considered statistically significant. Results. The mean serum ADAMTS-13 level in patients with PVT was significantly lower than that in patients without PVT (P=0.001) and controls (P=0.001). The mean serum ADAMTS-13 level in patients without PVT was significantly lower than that in controls (P=0.001). ADAMTS-13 levels were significantly associated with PVT accounting for the Child-Pugh or MELD score in the logistic regression model. Conclusions. Low serum ADAMTS-13 levels can be a useful indicator of portal thrombosis in patients with decompensated liver cirrhosis irrespective of Child-Pugh or MELD scores. Further research is needed to determine whether ADAMTS-13 levels will find use in everyday clinical practice.